The political technocracy: political capacity and executive governance in multiparty presidential systems - Lima, Iana Alves de (2024)
The assumption of labor division between bureaucrats and politicians and the hyperfocus on the type of recruitment has limited our understanding of how top administrations work from within, especially in places where patronage is widespread, such as Latin American countries. States in the region have become more complex not only in their size but also in their interactions (fragmented coalitions that require power-sharing, multilevel arenas, and society claims for political participation). This complexity requires a high-ranked bureaucrat who understands the technicalities of public management but is also perceptive about how these political interactions unfold within the executive branch. However, we know little about technical-political executive governance tasks and what is required from the individuals who perform them. What is technical-political governance, and how does it build state capacities? Through which processes do people develop the competencies to perform such tasks? I propose to open the “black box” of top administration to update our understanding of state capacity and its political dimension – the political capacity. I argue that political capacity is not only a static institutional feature but a toolbox of informal resources and strategies to manage the political relations inherent to policymaking. Through a grounded theory case study of Brazil, the dissertation aims to break down the process of building political capacity. First, I define the job by identifying eight technical-political governance tasks performed in the top executive office: leveraging, policy calibrating, political refereeing, playfield cultivation, shielding, advocating, upward agenda-building, and purposebuilding. Second, the research examines how these individuals develop competencies to perform such tasks. To perform such hybrid tasks, top appointees must amass an assorted toolbox of resources and learn “the way of doing public work” in this particular hybrid office. These combined resources and learning processes foster the emergence of a hybrid bureaucratic ethos – the political-technocratic ethos. This ethos allows states to deliver a virtuous politicization process, crafting the combination of technical and political resources into political capacity rather than predatory relations. Developing the political-technocratic ethos depends on crucial formative experiences: exposure to implementation, managing opposition, political translation, organizational mobility, and the praxis of the job. The findings have implications for principal-agent literature, as the building of political capacity relies on the collaborative capability of politicians and bureaucrats to integrate both technical and political knowledge to tackle higher office governance challenges, characterizing processes of expertise exchange.